2013
DOI: 10.1519/jsc.0b013e31825c2bdb
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Postactivation Potentiation and Power

Abstract: There is no clear agreement regarding the ideal combination of factors needed to optimize postactivation potentiation (PAP) after a conditioning activity. Therefore, a meta-analysis was conducted to evaluate the effects of training status, volume, rest period length, conditioning activity, and gender on power augmentation due to PAP. A total of 141 effect sizes (ESs) for muscular power were obtained from a total of 32 primary studies, which met our criteria of investigating the effects of a heavy preconditioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
374
8
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 399 publications
(419 citation statements)
references
References 53 publications
23
374
8
14
Order By: Relevance
“…Strength is one of the most critical attributes underlying success in sport [35,36]. The collective results of the present study, as well as those from Hoffman [18], suggest that changes in strength following supervised and non-supervised RT are enhanced by PA supplementation.…”
Section: Discussionsupporting
confidence: 72%
“…Strength is one of the most critical attributes underlying success in sport [35,36]. The collective results of the present study, as well as those from Hoffman [18], suggest that changes in strength following supervised and non-supervised RT are enhanced by PA supplementation.…”
Section: Discussionsupporting
confidence: 72%
“…Strength and power are two of the most critical attributes underlying success in sport (Robbins and Docherty 2005; Wilson et al 2012). These variables are intimately related and allow athletes to be successful in their respective sport (Cormie et al 2011a, b).…”
Section: Discussionmentioning
confidence: 99%
“…However, a consistent and significant finding of these studies is the high inter-individual variability in the voluntary PAP response. Increases (Baker, 2003; French et al, 2003; Mangus et al, 2006; Wilson et al, 2013), no change (Gossen and Sale, 2000; Gourgoulis et al, 2003; Jensen and Eben, 2003), as well as decreases (Chiu et al, 2003; Duthie et al, 2002) in muscular performance after the CA have been reported, what is indicative of a responder versus nonresponder phenomenon. Previous research has indicated that there are numerous factors that modulate PAP and its effect on performance in subsequent explosive activities.…”
Section: Introductionmentioning
confidence: 98%